The correlation that distance between world heritage sites and international airports has on visitation levels - Jocelyne Napoli; Ben Trapman (Goodwood Publishing, 2019)
Purpose: This article illustrates the comparative analysis that was performed on the 2018/2019 official databases of international airports and UNESCO WHS. This analysis was carried out to find connections between both air passenger and visitation levels for strategic leveraged purposes within tourism. Research methodology: Three databases were used in this analysis. The first database collects official data regarding airports such as their geographical position. The second includes data regarding the distance between WHS and international airports, while the third entails both air passenger arrivals and WHS visitation statistics. Results: Hence, this paper attempts to present the correlation that distance between WHS and International Airports has on visitation levels without claiming causation in any way. Contribution: The implications of this innovative research will stimulate future academic research interests and allow government departments, tourism entities, and other stakeholders to conduct further research and develop future strategies and action plans. Keywords: World heritage sites, Tourism, Air transport, Economics, Management